Laparoscopy in endometrial cancer - Valdivia, Henry (2015)
Endometrial cancer is one of the most frequent gynecological neoplasms. In our country it represents the third gynecological neoplasia following cervical and ovarian cancer. Most patients are seen in early stages of the disease, as uterine bleeding is an early manifestation. Among the endometrial cancer surgical approaches, midline laparotomy allows surgical staging. Vaginal approach in cases of marked obesity has limitations. Laparoscopy is a surgical technique of growing interest, with more evidence in the literature on its feasibility and advantages.